Blended Learning Modality in the New Normal Inputs Localized Learning Management System Proposal - Villasenor, Ma. Vivian S. (Future Science / FSH-PH Publications, 2022)
Blended learning is the combination of online distant learning being used in the schools. In the city where connectivity is proven, there are students who can adapt and yet there are also students who do not have a connectivity. In this way problem arises. We asked parents about this platform and from the parents themselves agreed from the school survey favored the digital modular learning. But in other localities preferred other modalities of learning. A lot of research involves teachers but seldom on the parents’ side. This is the researcher’s attempt to hear from the side of the parents and be a contributor to the effectiveness of Blended learning modality in Rizal High School. This study aimed to determine the Blended Learning Modality in the new normal and propose an input localized learning management system in the school. Specifically, it sought to answers the following problems: 1) what is the profile of parents’ respondents in terms of the following variables: Age; Educational background; Type of Internet connection; Gadget Access at home? 2) What is the assessment of respondents in the blended learning modality of the school in terms of the following variables: Platform & Support and Governance and Challenges encountered in the blended learning modality by the group of respondents? 3.) Is there significant relationship in the assessment of parents towards blended learning modality in terms of type of internet connection they have at home? 4. What proposal from the parents as inputs in the localized blended learning modality of Rizal High School? The descriptive method of research employed in this study. The subjects of the study were the parents at Rizal High School primarily the researcher’s handled section.